2000
DOI: 10.1086/302706
|View full text |Cite|
|
Sign up to set email alerts
|

Geographic Patterns of mtDNA Diversity in Europe

Abstract: Genetic diversity in Europe has been interpreted as a reflection of phenomena occurring during the Paleolithic ( approximately 45,000 years before the present [BP]), Mesolithic ( approximately 18,000 years BP), and Neolithic ( approximately 10,000 years BP) periods. A crucial role of the Neolithic demographic transition is supported by the analysis of most nuclear loci, but the interpretation of mtDNA evidence is controversial. More than 2,600 sequences of the first hypervariable mitochondrial control region w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
152
5
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(174 citation statements)
references
References 62 publications
14
152
5
3
Order By: Relevance
“…In general, our results are congruent with the apparent lack of mtDNA structure found for continental Europe compared with the more differentiated Mediterranean peninsulas (Simoni et al, 2000). These results are also in accordance with the different patterns found for the Y-chromosome haplogroup distribution in continental Europe compared with the Mediterranean peninsulas, with smooth clines and gradients apparent in continental areas (Rosser et al, 2000;Semino et al, 2000) contrasting to the focal expansions detected in Iberia (Flores et al, 2004), Italy and Greece (Di Giacomo et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, our results are congruent with the apparent lack of mtDNA structure found for continental Europe compared with the more differentiated Mediterranean peninsulas (Simoni et al, 2000). These results are also in accordance with the different patterns found for the Y-chromosome haplogroup distribution in continental Europe compared with the Mediterranean peninsulas, with smooth clines and gradients apparent in continental areas (Rosser et al, 2000;Semino et al, 2000) contrasting to the focal expansions detected in Iberia (Flores et al, 2004), Italy and Greece (Di Giacomo et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, diversity values for haplogroup V are significantly higher in Southern Iberia than in the Cornice and, confirming previous results (Simoni et al, 2000), we have not found significant latitudinal clines for this haplogroup. Furthermore, focussing on haplotype sharing, the Cornice is the most divergent area, despite North-east Iberia being the closest region to the rest of Europe.…”
Section: Phylogeographic Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of observed geographic structure in X-chromosome diversity in Europe resembles that of European mtDNA diversity 18 (though see Richards et al 20 ). However, many other previously studied genetic markers, including protein, Y-chromosome and autosomal DNA markers, have all described east -west gradients suggestive of immigration from the Near East.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, most studies of mtDNA in Europe have revealed a lack of clinal variation. 14,15,17,18 It is therefore likely that the higher rate of female gene flow in Europe is a major cause of the different patterns of X-chromosome markers when compared to autosomal and Y-chromosome DNA. Thirdly, and as suggested by Sokal et al, 41 the absence of clines at certain loci can be fully consistent with the demic-diffusion model, as only loci at which haplotype frequencies were markedly different for pre-Neolithic European hunter gatherers and Neolithic farmers are expected to show clinal variation across Europe.…”
Section: Discussionmentioning
confidence: 99%